Evaluation of simulated space weathering-based meteorite alteration and potential influence on mechanical deformation of rubble pile asteroids - Kereszturi, A.; Gyollai, I.; Biri, S.; Juhász, Z.; Király, Cs.; Pál, B. D.; Rácz, R.; Rezes, D.; Sulik, B.; Szabó, M.; Szalai, Z.; Szávai, P. (Frontiers in Astronomy and Space Sciences, 2025)
Asteroids with the potential to impact Earth have become a significant focus of scientific research and applied space technology. These bodies are expected to be key targets for mitigation actions and space mining activities in the coming decades. Understanding their material characteristics is challenging due to the effects of space weathering, which alters the mineral composition and structure of their surfaces, resulting in featureless infrared spectra. This study details laboratory tests of artificial solar wind effects on meteorites, revealing key changes including decreasing magnesium content in olivine, water loss-induced mineral changes, and general amorphization of the crystalline lattice. Although these alterations affect only a thin surface layer (and not the bulk regolith volume) of grains exposed on asteroid surfaces, they can influence the mechanical properties of most small (100 m-class) asteroids through physical surface contacts as most small asteroids are rubble piles with rotation, shape-altering grain migration, and surface mixing. The mechanical properties of only a very thin surface layer of specific grains are influenced; however, the behavior of granular aggregates with such influenced surfaces could be mixed by the YORP effect. This study reviews established findings, explores potential implications for asteroid behavior, and identifies future research directions.